Neutrophil/Lymphocyte Ratio Can Predict Postoperative Mortality in Patients with Chronic Thromboembolic Pulmonary Hypertension - YILDIZELİ, BEDRETTİN; BEKİROĞLU, GÜLNAZ NURAL (MEDICAL TRIBUNE INC, 2015)
Objective: The aim of our study was to investigate clinical importance of neutrophil/lymphocyte ratio in patients with Chronic thromboembolic pulmonary hypertension. Methods: 125 consecutive patients with a diagnosis of Chronic thromboembolic pulmonary hypertension were operated pulmonary thromboendarterectomy in our center between February 2011 and August 2013. 106 patients included into the study due to limitations. The patients were classified into two groups as patients discharged alive (Group 1) and those dying in the hospital (Group 2). Baseline neutrophil/lymphocyte ratio level was measured by dividing neutrophil count to lymphocyte count. Results: 84 patients (79%) were in Group 1, 22 patients (21%) were in Group 2. Patients with higher neutrophil/lymphocyte ratio in admission have a significantly higher mortality rate and postoperative pulmonary vascular resistance was found statistically significant variable to predict the mortality. Receiver operator characteristic (ROC) analysis revealed that using a cut-off point of 2.54, admission neutrophil/lymphocyte ratio predicts mortality. Also, correlation analysis showed a significant correlation between preoperative pulmonary vascular resistance and neutrophil/lymphocyte ratio. Conclusion: The neutrophil/lymphocyte ratio level may be a useful and noninvasive biomarker for operative risk stratification for mortality after pulmonary thromboendarterectomy.
Keywords: Chronic thromboembolic pulmonary hypertension; pulmonary thromboendarterectomy; pulmonary vascular resistance; inflammation; Neutrophil/lymphocyte ratio; ARTERIAL-HYPERTENSION; OXIDATIVE STRESS; PROGNOSTIC VALUE; ENDARTERECTOMY; EXPERIENCE